Islam dan Kolonialisme: Sayyid Usman dan Islam di Indonesia Masa Penjajahan - Burhanudin, Jajat (Studia Islamika, 2015)
Nico J.G. Kaptein, Islam, Colonialism, and the Modern Age in the Netherlands East Indies: A Biography of Sayyid ‘Uthman (1822-1914), (Leiden & Boston: Brill. 2014), xv + 317 pages.The book reviewed was the published result of long, scholarly research efforts. Nico Kaptein, the writer, presents a biography of Sayyid Uthman, an ‘ālim out of the Hadrami community in nineteenth century Dutch East Indies.  The biography is comprehensive in nature. More importantly, the author shows this Muslim scholar as having partipated in, and therefore contributed to, the structuring of Indonesian Islam. The content arrangement of the book follows the life story of Sayyid Uthman.  As an ‘ālim, Sayyid Uthman engaged in current Islamic issues in the Indies, and served as an advisor for Arab affairs for the Dutch colonial government. His being an advisor has long been a subjet of debate. For Muslims, the decision of Sayyid Uthman to cooperate with the government is unacceptable. The Dutch are not only unblievers (kāfir) but also anti-Islam. It is the issue of Uthman being an advisor that becomes the main discussion of the book.DOI: 10.15408/sdi.v22i1.1391